A Comparative Study Of Principle Of Guilt In The Provision Of Indonesian And English Criminal Law - Rr. Dijan Widijowati (KRTHA BHAYANGKARA, 2024)
The principle of guilt is universally recognized by worldwide nations as the absolute basis of a sentenced person. Principle of No Crime without Guilt or Principle of Guilt contains an understanding that any person committing an action, which contradicts with applicable criminal law, can be sentenced due to the absence of guilt in his/her actions. The principle of no crime without guilt is closely related to principle of legality, stating that there is no crime without previous arrangement. It means that the element of guilt can be attached if there are available regulations stipulating that the committed act is criminal act. This research aims to compare the principles of guilt in Indonesian and English Criminal Law. The method employed in this research was a normative-legal method based on secondary data as research material so that it focused on theoretically speculative measures and normative and qualitative analysis, which were the focus of the discussion on how principle of guilt in the criminal liability in Indonesia compared to with principle of guilt in the UK. The results of the study show that there were differences in the application of the principle of guilt in Indonesian and English criminal law.